EFEKTIVITAS OPERASIONAL PERPUSTAKAAN SMA NEGERI 11 BANDAR LAMPUNG SELAMA PANDEMI COVID-19 - Arnila Purnamayanti; Hanun Agus Trivio Purwanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2022)
The school library is one of the mandatory facilities owned by every school. and also become a center for reading books that are recreational to allow students can develop their creativity and imagination. The author did research with the attached title to measure the extent to which the effectiveness operations of a school library in implementing closed services in situations that do not allow students and visitors to visit library. The writing method in writing the final project is a qualitative method. Data collection techniques through interviews, observation, documentation, and also studies references. The result of writing this final project is the operational effectiveness of the SMA library Negeri 11 Bandar Lampung has not run effectively. This can be measured in the use of aspects with effectiveness guidelines. In its application, there are some results conform to regulatory standards as well as appropriate aspects. From the aspect regulations that are not in accordance with standard provisions with regulatory aspects on school library, then the aspect of the goal that has not been able to maximize activities learning is due to the non-optimal delivery of materials, while the functional aspects who have not reached library regulatory standards by limiting activities in library. For the planning aspect where the library has other plans with according to standard library regulations that provide access to visitors. Based on the results of the study, it was concluded that the operational effectiveness of library during the Covid-19 pandemic is not effective, because there are aspects regulations, aspects of objectives and aspects of functions that do not meet the standards.